Analisis pembelajaran aspek kognitif materi pendidikan jasmani olahraga dan kesehatan sma/smk di daerah istimewa yogyakarta - Ahmad Rithaudin; Indah Prasetyowati Tri Purnama Sari (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2019)
Penelitian ini dilatarbelakangi oleh permasalahan ditemuinya kesulitan guru dalam penyusunan Rencana Pelaksanaan Pembelajaran (RPP) dengan isi materi yang mencakup tiga tujuan utama pembelajaran yaitu kognitif, afektif dan psikomotor. Penelitian ini bertujuan untuk menganalisis pembelajaran pada aspek kognitif yang terdapat dalam RPP mata pelajaran penjasorkes di SMA/SMK di Daerah Istimewa Yogyakarta (DIY). Desain dalam penelitian ini adalah deskriptif kuantitatif, dengan metode analisis dokumen. Subyek dalam sekolah mitra UNY pada tahun 2015 yang berjumlah 21 sekolah. Adapun data yang didapatkan adalah 19 RPP dari 19 sekolah. Instrumen dalam penelitian ini adalah lembar analisis dokumen. Hasil yang didapatkan dalam penelitiann ini dapat disimpulkan bahwa secara umum terdapat materi pembelajaran pada aspek kognitif dalam RPP pembelajaran penjasorkes SMA Mitra UNY di DIY. Kemudian jika analisis dilakukan terhadap indikator yang dikembangkan, indikator yang berkaitan dengan pengembangan kompetensi kognitif siswa hanya muncul di dalam RPP yang kembangkan dengan kurikulum tahun 2013. Untuk uraian materi yang dikembangkan, hampir semua RPP yang kembangkan secara minimal telah mencantumkan materi yang berkaitan dengan pengembangan kompetensi kognitif siswa. Kecenderungan materi lebih lengkap apabila RPP tersebut disusun berdasar kurikulum tahun 2013. Learning analysis of cognitive aspects of sports and health education materials in high school and vocational school of yogyakarta special region AbstractThis research is motivated by problems encountered by the teacher's difficulties in the preparation of the lesson plan (RPP) with the contents of the material which includes three main objectives of learning, namely cognitive, affective and psychomotor. This study aims to analyze learning on cognitive aspects contained in the RPP of physical education courses in high schools / vocational schools in the Special Region of Yogyakarta (DIY). The design in this study is descriptive quantitative, with document analysis methods. The subjects in the Universitas Negeri Yogyakarta (UNY) partner schools in 2015 were 21 schools. The data obtained are 19 lesson plans from 19 schools. The instrument in this study is a document analysis sheet. The results obtained in this research can be concluded that in general there are learning material on cognitive aspects in the lesson plan for physical education in high school UNY partners in Special Region of Yogyakarta (DIY). Then if the analysis is carried out on the indicators developed, indicators relating to the development of student cognitive competencies only appear in the RPP developed with the 2013 curriculum. For the description of the material developed, almost all RPPs that have developed have included material related to competency development. Cognitive students. Material trends are more complete if the RPP is prepared based on the 2013 curriculum.